Interview with Shigechika Kobara, Kimi Kobara and Yoshiko Tachibana (1980)
Yoshiko Tachibana interviews Shigechika and Kimi Kobara about their experiences living in Seattle, Los Angeles, Guadalupe, and Lompoc California in the years before the Second World War. Tachibana then asks the Kobaras about their time in the internment camps, in Fresno, Bismark, and Gila. They also discuss Kimi Kobara's immigration to the United States as a picture bride, the Japanese Christian Church and Buddhist temple in Arroyo Grande, farming and agricultural, and finally the encounters between the Kobara family and other local families upon returning to their home in 1945. English transcription available, contact Special Collections and Archives to access. See also Yoshiko Tachibana's 1982 Senior Project 'Oral Histories of Japanese-Americans in San Luis Obispo County' https://cpslo-primo.hosted.exlibrisgroup.com/permalink/f/39e239/01CALS_ALMA991000328749702920. Includes both an original transcription in Japanese, and an English translation of the original transcription.